Usability testing of a wireless individual indicator system application: monitoring exposure to outdoor air pollution among Malaysian traffic police - Mohamad Jamil, Putri Anis Syahira; Karuppiah, Karmegam; Naeini, Hassan Sadeghi; Mohammad Yusof, Nur Athirah Diyana; Mohd Suadi Nata, Dayana Hazwani; Abdul Aziz, Nurhanim; Mohd Tamrin, Shamsul Bahri (SAGE Publications, 2022)
Objectives: Designs for low-cost air monitors and associated performance data appear in many peer-reviewed articles; however, few manuscripts provide feedback from end user's experiences or comprehensive evaluation. The present study addresses the usability of the wireless outdoor individual exposure indicator system from the viewpoint of the Malaysian Traffic Police (end users). This study is one of the first to chronicle end user experiences for low-cost pollution sensing. Method: The evaluation involved 12 target end users to assess the usability of a prototype for Malaysian Traffic Police to manage their exposure to outdoor air pollution. The test evaluation includes a pre-test, post-task and post-test questionnaire (Post-Study System Usability Questionnaire). The main components in this Post-Study System Usability Questionnaire are Overall satisfaction, System Usefulness, Information Quality and Interface Quality. Findings: The results of the Post-Study System Usability Questionnaire indicated the mean score of the Overall satisfaction item (2.33), System Usefulness (2.25), Information Quality (2.36) and Interface Quality (2.17) on a scale of 1–10. Prototype users were satisfied with the system because the score is close to 1 on the Post-Study System Usability Questionnaire. Conclusions: A user-friendly wireless outdoor individual exposure indicator system is now available for Malaysian Traffic Police. Users have stated that they are happy to use the system at work. However, in addition to more technological advances, practical implementation requires evidence supporting its efficacy, viability and effectiveness.